The Effect of Work Ability on Employee Creativity in the Digital Era in Mediating Work Motivation and Job Opportunities in Company Employees START UP Sleman, Yogyakarta - Jovie, Jovie Armelinda Putri Seso; Muafi (Jurnal Economic Resource, 2024)
This study examines the effect of employee work ability on work creativity in the digital era mediated by work motivation and job opportunities. This research was conducted on Star Up companies spread across Sleman district, Yogyakarta. This study used quantitative methods using sampling methods that were the same as the population in this study. The sample that met the criteria amounted to 105 respondents. Test the hypothesis of this study using Smart PLS version 3.2.9. The results obtained that Employee work ability has a positive and significant effect on work motivation, Employee work ability has a positive and significant effect on job opportunities, Work motivation has a positive and significant effect on Employee Creativity in the digital era, Job opportunities have a positive and significant effect on work motivation For Employee Creativity in the digital era, there is a mediating role in the relationship between Employee Work Ability and Employee Creativity in the digital era in Job Motivation mediation, and there is a mediating role in the relationship between Employee Work Ability and Employee Creativity in the digital era in Job Opportunity mediation.